Hip Tenosynovial Giant Cell Tumor without Recurrence in a 9-Year Follow-Up - Seyyed-Morteza Kazemi; Seyyed-Mohsen Hosseininejad (Case Reports in Orthopedics)
Background. Tenosynovial giant cell tumors are a benign but rare condition with potentially aggressive tumor-like traits which should be considered in young patients with monoarticular joint involvement. Case Presentation. This report presents a 31-year-old otherwise healthy woman with a right hip pain. Clinical and histopathological investigations revealed the diagnosis of diffuse-type tenosynovial giant cell tumor of the hip (the diffuse intra-articular form of PVNS). Open synovectomy and tumor resection and surgical dislocation of the hip were performed. She was free of symptoms and recurrence within a 9-year-follow-up period. Conclusion. Open synovectomy and tumor resection through surgical dislocation of the hip without adjutant radiotherapy could be a reliable choice for the localization of the hip.